Circadian clocks' interactions with oxygen sensing and signalling. (19th January 2022) - Adamovich, Yaarit; Dandavate, Vaishnavi; Asher, Gad
Abstract: In mammals, physiology and metabolism are shaped both by immediate and anticipatory responses to environmental changes through the myriad of molecular mechanisms. Whilst the former is mostly mediated through different acute signalling pathways the latter is primarily orchestrated by the circadian clock. Oxygen is vital for life and as such mammals have evolved different mechanisms to cope with changes in oxygen levels. It is widely accepted that oxygen sensing through the HIF‐1 signalling pathway is paramount for the acute response to changes in oxygen levels. Circadian clocks are molecular oscillators that control 24 hours rhythms in various aspects of physiology and behaviour. Evidence emerging in recent years points towards pervasive molecular and functional interactions between these two pathways on multiple levels. Daily oscillations in oxygen levels are circadian clock‐controlled and can reset the clock through HIF‐1. Furthermore, the circadian clock appears to modulate the hypoxic response. We review herein the literature related to the crosstalk between the circadian clockwork and the oxygen‐signalling pathway in mammals at the molecular and physiological level both under normal and pathologic conditions.